The Hamiltonian Structure and Algebrogeometric Solution of a 1 + 1-Dimensional Coupled Equations - Hongfei Pan; Tiecheng Xia (Journal of Applied Mathematics)
A 1 + 1-dimensional coupled soliton equations are decomposed into two systems of ordinary differential equations. The Abel-Jacobi coordinates are introduced to straighten the flows, from which the algebrogeometric solutions of the coupled 1 + 1-dimensional equations are obtained in terms of the Riemann theta functions.